2021
DOI: 10.1186/s12891-021-04830-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tourniquet on short-term outcomes in opening wedge high tibial osteotomy with modern tranexamic acid protocols: a retrospective cohort study

Abstract: Background The use of a tourniquet during high tibial osteotomy (HTO) is a routine procedure, but there is currently no research on the benefits and potential risks of tourniquet use during HTO. The aim of this study was to investigate the impact of tourniquet on perioperative blood loss, early functional recovery and complications in opening wedge HTO with modern tranexamic acid protocols. Methods This was a retrospective cohort study of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…It has been found that the application of TXA in intra-articular cavity injection can further enhance the hemostatic effect because intra-articular TXA targets active bleeding sites and increases the stability of the fibrin clot, thereby avoiding blood loss from the tissue surface [ 24 ]. It has been reported that intra-articular injection did not increase the incidence of VTE [ 25 ]; however, uncertainties remain on the risk of complications associated with intravenous injection. In the present study, both intravenous and intra-articular injections were performed, and no significant differences were found between the two groups in terms of postoperative coagulation indexes ( P > 0.05), serological examination showed no statistical differences in D-D levels between the two groups, and the absence of VTE in both groups was confirmed by imaging, indicating no increase in the probability of thrombosis in diabetic patients with intravenous high-dose TXA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the application of TXA in intra-articular cavity injection can further enhance the hemostatic effect because intra-articular TXA targets active bleeding sites and increases the stability of the fibrin clot, thereby avoiding blood loss from the tissue surface [ 24 ]. It has been reported that intra-articular injection did not increase the incidence of VTE [ 25 ]; however, uncertainties remain on the risk of complications associated with intravenous injection. In the present study, both intravenous and intra-articular injections were performed, and no significant differences were found between the two groups in terms of postoperative coagulation indexes ( P > 0.05), serological examination showed no statistical differences in D-D levels between the two groups, and the absence of VTE in both groups was confirmed by imaging, indicating no increase in the probability of thrombosis in diabetic patients with intravenous high-dose TXA.…”
Section: Discussionmentioning
confidence: 99%
“…These strict bleeding-control procedures help to minimize postoperative swelling due to hemorrhage, without an indwelling drain ( Table 2 ). As for OWHTO 10 or TKA, 11 the safe nontourniquet procedure may decrease the intraoperative/perioperative risks of complications such as bleeding, hematoma, or infection and may enhance postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tranexamic acid reduces postoperative bleeding and hematoma [4, 15]. No tourniquet was used and minimally‐invasive surgical techniques were applied, which might be beneficial with regard to wound complications and infections [13, 35]. Additionally, all surgeries were performed by high‐volume osteotomy specialists.…”
Section: Discussionmentioning
confidence: 99%